Crystal structure of 3-(4-bromophenyl)-5-methyl-1H-pyrazole, C10H9BrN2 - Kočović David; Mugoša Snežana; Shova Sergiu; Tomić Zoran D.; Jaćimović Željko K. (Zeitschrift für Kristallographie - New Crystal Structures)
C10H9BrN2, orthorhombic, P212121 (no. 19), a = 5.9070(3) Å, b = 9.2731(7) Å, c = 17.5641(14) Å, V = 962.09(12) Å3, Z = 4, Rgt(F) = 0.0504, wRref(F2) = 0.0947, T = 293(2) K.